2022
DOI: 10.3389/fmed.2022.1069013
|View full text |Cite
|
Sign up to set email alerts
|

Performance of leflunomide as a steroid-sparing agent in giant cell arteritis: A single-center, open-label study

Abstract: BackgroundThe management of giant cell arteritis (GCA) remains challenging and many patients require prolonged glucocorticoid treatment due to high disease relapse rates. We aimed to evaluate the role of leflunomide as a steroid-sparing agent in GCA.MethodsThis prospective open-label study included patients diagnosed with GCA between July 2014 and August 2020 and followed them for 96 weeks. At the time of diagnosis all patients received treatment following a predefined glucocorticoid regimen. At week 12 of fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The trial concluded that leflunomide was an effective steroid-sparing agent in three-quarters of patients and enabled a lower cumulative corticosteroid dose. 48 Other prospective observational series have also demonstrated the efficacy and safety of leflunomide as a steroid-sparing agent in GCA. 49…”
Section: Leflunomidementioning
confidence: 99%
“…The trial concluded that leflunomide was an effective steroid-sparing agent in three-quarters of patients and enabled a lower cumulative corticosteroid dose. 48 Other prospective observational series have also demonstrated the efficacy and safety of leflunomide as a steroid-sparing agent in GCA. 49…”
Section: Leflunomidementioning
confidence: 99%
“…A metaanalysis of the methotrexate trials [70] demonstrated that use of methotrexate alongside glucocorticoids reduced relapses, cumulative glucocorticoid dose requirements, and increased the chance of sustained discontinuation of glucocorticoids, without any difference in adverse events between trial arms [70]. Other csDMARDs that have been utilised, but have not been adequately tested for efficacy in clinical trials, include leflunomide [71], azathioprine [72], and mycophenolate [73]. Cyclophosphamide is occasionally used for very severe or refractory cases, based on protocols developed in other types of vasculitis, but toxicity is high [74].…”
Section: Oral Immunomodulatory Agentsmentioning
confidence: 99%
“…Leflunomide, another conventional synthetic DMARD suppresses the production of pro-inflammatory cytokines through the activation of dendritic cells and modifies the action of the T-cell response in GCA [126]. A number of studies support its use, but as of yet there is no randomised controlled evidence for its directed use [127][128][129][130].…”
Section: Management Of Gcamentioning
confidence: 99%